(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2023)
The academic environment is a good place to develop an ethical competency. The overall goal of the project is to support the development of ethical competence in nursing students and to help them deal with ethical issues and dilemmas. Method: An integrative review of scientific studies focused on the strategies used to develop ethical competence and to support resolution of ethical issues and dilemmas among nursing students was conducted in the following databases: CINAHL, PubMed, Embase, Education Source and ERIC 2009-2019). Two reviewers worked independently. The final inclusion was decided after review of all agrees and disagrees with the principal investigator of the project. The Mixed Methods Appraisal Tool (MMAT) was used to assess the quality of studies for this review. The included studies met the following inclusion criteria: a) derived from a scientific study; b) involved nursing students; c) concerning teachings methods; d) concerning ethical competence; e) being published in English or French. Conference papers, proceedings, literature review, non-intervention studies and studies focused in other health specialties were excluded. Results: Electronic searching yielded a total of 2,704 citations, 21 publications were selected in the final review. Discussion: The main results showed several gaps in the methodologies used. The first gap is the lack of consensus on the definition of ethical competence resulting in the absence of a specific theoretical framework for teaching it. All the interactive and multimodal teaching methods, with active student engagement were effective and enabled them to develop ethical competencies and related communicative skills, interpersonal skills, collaboration, and critical thinking. Among the pedagogical approaches, the conventional, theoretical approach was rated the least by the students, but not necessarily the least effective. Conclusion: Circumscribing the definition of ethical competence and developing a theoretical model adapted to nursing should remain a priority in order to better guide teachers. Multimodal teaching methods seem to be unanimously accepted and meet the learning objectives set by the various studies.